Regulation of dendritic cell activation by microRNA let-7c and BLIMP1 - Sun Jung Kim; Peter K. Gregersen; Betty Diamond (2013)
Mice with a DC-specific deletion of the transcriptional repressor B lymphocyte–induced maturation protein-1 (Blimp1) exhibit a lupus-like phenotype, secondary to enhanced DC production of IL-6. Here we explored further phenotypic changes in Blimp1-deficient DCs, the molecular mechanism underlying these changes, and their relevance to human disease. Blimp1-deficient DCs exhibited elevated expression of MHC II, and exposure to TLR agonists increased secretion of proinflammatory cytokines. This phenotype reflects enhanced expression of the microRNA let-7c, which is regulated by BLIMP1. Let-7c reciprocally inhibited Blimp1 and also blocked LPS-induced suppressor of cytokine signaling-1 (SOCS1) expression, contributing to the proinflammatory phenotype of Blimp1-deficient DCs. DCs from Blimp1 SLE-risk allele carriers exhibited analogous phenotypic changes, including decreased BLIMP1 expression, increased let-7c expression, and increased expression of proinflammatory cytokines. These results suggest that let-7c regulates DC phenotype and confirm the importance of BLIMP1 in maintaining tolerogenic DCs in both mice and humans.